2004
DOI: 10.3748/wjg.v10.i16.2379
|View full text |Cite
|
Sign up to set email alerts
|

DA-9601 for erosive gastritis: Results of a double-blind placebo-controlled phase III clinical trial

Abstract: AIM:To determine the efficacy and safety of DA-9601 on erosive gastritis versus cetraxate as a standard drug by gastrointestinal endoscopy. METHODS:Five hundred and twelve patients with erosive gastritis were divided into three groups. The groups received 180 mg or 360 mg of DA-9601, or 600 mg of cetraxate (Neuer TM ) t.i.d. for 2 wk, respectively. Endoscopic observations were performed before and 2 wk after the treatment, and the cure and improvement rates were investigated. RESULTS:Of the 512 intention-to-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…For example, it has been reported that a pharmaceutical agent containing eupatilin protects against gastric mucosal injury [27] and carrageenan-induced paw edema [24]. Moreover, animal studies have shown that eupatilin ameliorates acetaminophen-and carbon tetrachloride-induced acute liver injury [28] and dimethyl nitrosamine-induced liver fibrosis [29].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that a pharmaceutical agent containing eupatilin protects against gastric mucosal injury [27] and carrageenan-induced paw edema [24]. Moreover, animal studies have shown that eupatilin ameliorates acetaminophen-and carbon tetrachloride-induced acute liver injury [28] and dimethyl nitrosamine-induced liver fibrosis [29].…”
Section: Introductionmentioning
confidence: 99%
“…Eupatilin has been used in clinic as a drug for gastritis and peptic ulcer (36). Therefore, we expect that eupatilin could be repositioned for treating ciliopathy patients carrying CEP290 mutations.…”
Section: This Suggests That Although Eupatilin Can Promote Ciliogenesmentioning
confidence: 99%
“…6 It has been used to treat erosive gastritis and atrophic gastritis, 22 and its efficacy against erosive gastritis was reported to be higher than that of cetrexate. 23 Even the susceptibility of patients using NSAIDs to gastric mucosal damage by alcohol was also shown to be reduced by DA-9601. 22 The present study demonstrated that the production and secretion of ghrelin increased more in DA-9601-pretreated rats subsequently exposed to alcohol or indomethacin than in the placebo-pretreated rats suggesting that increased production of ghrelin may be responsible for the gastro-protective effect of DA-9601.…”
Section: Discussionmentioning
confidence: 99%